Gerakan Sosial Petani Pagar Batu - Puspitasari, Yuni; Kinseng, Rilus A; Saharuddin, Saharuddin (JURNAL SOSIAL HUMANIORA (JSH), 2023)
The emergence of the Pagar Batu peasant social movement can be attributed to the expression of dissent towards companies involved in oil palm plantations. The conversion of agricultural land into these plantations has posed a myriad of challenges for the peasants. The primary objective of this study was to investigate the underlying issues between the oil palm plantation company and the Pagar Batu Peasant community, while also seeking to comprehend the social movement instigated by the peasants to address the impact of these plantations. The research was conducted using a qualitative method, adopting a case study approach, and gathering primary data through observations, in-depth interviews, and focus group discussions, while secondary data was obtained from documents and profiles. The research findings revealed that the emergence of the social movements primarily resulted from concerns pertaining to conflicting land ownership, monopolization of palm oil, alterations in land utilization, and transformations in people's means of livelihood. The Pagar Batu Peasants openly conducted their social movements to raise awareness and gain attention, employing various strategies such as demonstrations, land reclamation, and, on certain occasions, resorting to physical confrontation